2010
DOI: 10.1123/ijspp.5.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Talent Development in Adolescent Team Sports: A Review

Abstract: Traditional talent development pathways for adolescents in team sports follow talent identification procedures based on subjective games ratings and isolated athletic assessment. Most talent development models are exclusive rather than inclusive in nature. Subsequently, talent identification may result in discontentment, premature stratification, or dropout from team sports. Understanding the multidimensional differences among the requirements of adolescent and elite adult athletes could provide more realistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
129
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 52 publications
1
129
0
9
Order By: Relevance
“…We found seated height to be a significant predictor of 20 m sprint time (32%), however height was not included in the analysis due to issues with collinearity (e.g., seated height and leg length). The RAE is well documented in the football codes (Mujika et al, 2009;Till et al, 2010;Williams, 2010) and has been shown to result in short-term and long-term differences in sport outcomes as a result of birth date (Burgess & Naughton, 2010;Cobley et al, 2009;Meylan, Cronin, Oliver, & Hughes, 2010), although the phenomenon is not always associated with significant advantages in physical fitness or transition to professional ranks (Carling, Le Gall, Reilly, & Williams, 2009). Not surprisingly, the RAE is primarily attributed to differences in chronological age, although age category, skill level and sport context also contribute to RAE (Cobley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We found seated height to be a significant predictor of 20 m sprint time (32%), however height was not included in the analysis due to issues with collinearity (e.g., seated height and leg length). The RAE is well documented in the football codes (Mujika et al, 2009;Till et al, 2010;Williams, 2010) and has been shown to result in short-term and long-term differences in sport outcomes as a result of birth date (Burgess & Naughton, 2010;Cobley et al, 2009;Meylan, Cronin, Oliver, & Hughes, 2010), although the phenomenon is not always associated with significant advantages in physical fitness or transition to professional ranks (Carling, Le Gall, Reilly, & Williams, 2009). Not surprisingly, the RAE is primarily attributed to differences in chronological age, although age category, skill level and sport context also contribute to RAE (Cobley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Athletes will face many challenges over time (Bloom, 1985;MacNamara, Holmes, & Collins, 2008), whether it be performance, development or lifestyle-related (Martindale, Collins, & Abraham, 2007), and personal characteristics such as intrinsic motivation have been shown to play a crucial part in overcoming those challenges and becoming a world class athlete over time (Abbott & Collins, 2004;Bloom, 1985;Martindale et al, 2007). Furthermore, athletes who maintain strong task orientation have been shown to be less stressed, better learners and more intrinsically motivated (Deci & Ryan, 2008;Duda & White, 1992), which leads to less burn-out and drop out through the system (Burgess & Naughton, 2010). Although this is just one example, it highlights the need to understand how personal characteristics are influenced by the talent development environment.…”
mentioning
confidence: 93%
“…A consistent criticism of most TID models is that they are both exclusive and do not comprehensively take into account the multidimensional aspects of TID to ensure that realistic goals are set for those who are included (Vaeyens, Lenoir, Williams, & Philippaerts, 2008). This is important if you want to avoid dropout and ensure that appropriate reward schemes reflect the relevant needs of long-term and successful development (Burgess & Naughton, 2010). Singapore has a total land area of about 700 square kilometers and a total population of less than five million.…”
mentioning
confidence: 98%
“…Several variables have been investigated to define the elite athlete, including anthropometric and physiologic characteristics, 2,3,33-35,45,61,62,66,77,74,92 balance, 44 the role of the athlete on the team, 11,77 length of training, 45 type of performance training, 13,24,44,46,65 talent development and maturation, 1,3,19,66,74,88 and physical performance. 7,15,91 The multiple variables attest to the complexity of the elite athlete.…”
mentioning
confidence: 99%